ISSUES OF ENSURING THE EFFECTIVENESS OF CORPORATE FINANCIAL MANAGEMENT IN IMPORTING ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
The thesis examines the key challenges and approaches to ensuring the effectiveness of corporate financial management in importing enterprises. It analyzes how strategic budgeting, internal financial control, risk management, investment strategies, and financial information systems influence financial stability, liquidity, and overall performance. The study also explores the role of corporate governance principles and institutional frameworks in optimizing financial decision-making processes.
Keywords: Importing enterprises, corporate financial management, financial efficiency, budgeting, internal control, risk management, investment strategy.